What sustains informality? A study of the interactions between formal- and informal-sector firms - Ajit Mishra (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We consider two vertical links between informal- and formal-sector firms and study their implications. In one case, the final products produced by the formal- and informal-sector firms are vertically differentiated in terms of quality, and the size of the informal sector demand is related to the income distribution. Our paper studies the implications of this quality choice for the size of the informal sector. In the other case, the informal-sector firm produces an intermediate good as an input for the formal-sector firm. This has several possible implications for the growth of the informal sector in terms of both output and productivity.
Keywords: O15; O17; K4; H8; 330; informal sector; income distribution; demand; quality; inputs